Análise filogenética da família multigênica da catalase em angiospermas e expressão in silico na espécie Zea mays - Lemos, Moaciria de Souza (2019)
Throughout evolution, plants have developed strategies to mitigate the negative effects of the environmental stresses to which they are exposed. Among these strategies, the development of an antioxidant system plays a primordial role in dealing with molecules or free radicals harmful to the cell. Catalase is an enzyme that is part of this line of defense, metabolizing H2O2, which at high concentrations causes harmful effects on cells. In plants, catalase is generally encoded by a multigenic family of up to three genes.However, the distribution as well as the physiological function of each gene member are still poorly understood subjects. This work aimed to analyze the structure and phylogenetic distribution of the catalase genes in angiosperms as well as their functionality (expression) in different tissues during development and stress conditions in corn. The catalase genes were annotated and the cDNA sequences obtained were used to construct the phylogenetic tree through Bayesian methodology and also to determine the gene structure. Gene expression was evaluated in corn transcriptomic data (in silico) using the HTSeq tool. From the phylogenetic analysis four catalase subfamilies were identified in angiosperms (CAT2, CAT3, CAT1 and CAT4). The first two found only in species of monocots, the third shared by both clades and the last one found only in eudicots. Gene structure data suggest that gene evolution occurred through predominantly introns deletion events and through duplication. Expression analysis revealed that the cat2 and cat3 genes are expressed in the root under dry condition and under fungus attack, respectively. Both genes had expression in the germinated grain and mature foliar tissue. The cat1 gene was expressed only in reproductive tissues. All three genes studied have expression profile dependent on tissue and stage of development of the plant. The data obtained in this work contribute to elucidate the evolutionary distribution of the catalase genes in plants, generating information to establish a broader classification seeking interrelationship between phylogeny, structure and gene function.